Upregulation of retinal dehydrogenase 2 in alternatively activated macrophages during retinoid-dependent type-2 immunity to helminth infection in mice. - Mara J Broadhurst; Jacqueline M Leung; K C Lim; Natasha M Girgis; Uma Mahesh Gundra; Padraic G Fallon; Mary Premenko-Lanier; James H McKerrow; Joseph M McCune; P'ng Loke (PLoS Pathogens)
Although the vitamin A metabolite retinoic acid (RA) plays a critical role in immune function, RA synthesis during infection is poorly understood. Here, we show that retinal dehydrogenases (Raldh), required for the synthesis of RA, are induced during a retinoid-dependent type-2 immune response elicited by Schistosoma mansoni infection, but not during a retinoid-independent anti-viral immune response. Vitamin A deficient mice have a selective defect in T(H)2 responses to S. mansoni, but retained normal LCMV specific T(H)1 responses. A combination of in situ imaging, intra-vital imaging, and sort purification revealed that alternatively activated macrophages (AAMφ) express high levels of Raldh2 during S. mansoni infection. IL-4 induces Raldh2 expression in bone marrow-derived macrophages in vitro and peritoneal macrophages in vivo. Finally, in vivo derived AAMφ have an enhanced capacity to induce Foxp3 expression in CD4+ cells through an RA dependent mechanism, especially in combination with TGF-β. The regulation of Raldh enzymes during infection is pathogen specific and reflects differential requirements for RA during effector responses. Specifically, AAMφ are an inducible source of RA synthesis during helminth infections and T(H)2 responses that may be important in regulating immune responses.